Collaboration, narrative, and inquiry that honor the complexity of teacher education - Lachuk, Amy Johnson; Gísladóttir, Karen Rut; DeGraff, Tricia (Advances in teacher education., 2021)
"Collaboration, Narrative, and Inquiry that Honor the Complexity of Teacher Education presents a narrative exploration of three teacher educators' collaborative and transnational inquiry into their practices. Through carefully selected narratives, the authors describe how they enacted a practice-based approach in their teacher education courses. The authors present challenges and complexities they encountered as teacher educators in trying to prepare preservice teacher candidates for the realities of the classroom"--